Workers at risk: voices from the workplace - Nelkin, Dorothy; Brown, Michael S. (University of Chicago Press, 1984)
"This documentary account of workers routinely exposed to chemicals on the job is based on 75 interviews with chemical operatives, maintenance workers, technicians in chemical, pharmaceutical, food processing and industrial plants, laboratory technicians, fire fighters, and railroad and health care workers. Topics covered include: the jobs and the risks involved with chemicals; illnesses, fears and responsibility; protection, adaptation and action; recourse in the case of hazards; controlling risks on the job."